The Effectiveness of Plasticine and Collage Play Therapy in Preschool Children Against Gadget Addiction in Gondosuli Village - Abdurrohim, Abdurrohim; Munir, Zainal; Heru, Maulidiyah Junnatul Azizah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to find out how effective plasticine and collage play therapy methods are for children who are addicted to gadgets. Where the continuous use of gadgets in children will have a negative impact on children's behavior patterns in their daily lives, children who tend to constantly use gadgets will be very dependent and become activities that children must and routinely do in their daily activities. With plasticine play therapy and collage, it is a good activity to reduce the use of gadgets. The goal of plasticine and collage play therapy is to divert children from excessive playing with gadgets. In providing play therapy, it must be adjusted to the age and developmental stage of the child. The method used in this study is a quantitative method. The design used is a two group pre-post test design. The instrument used is a questionnaire (questionnaire). Determination of the sample in this study using a sampling technique with purposive sampling technique. Data analysis in this study used the Friedman test. The results showed that there was an effect of giving Plasticine, Collage, Plasticine and Collage play therapy to preschool children with a p-value of 0.000 (p <0.05) where H0 was rejected and Ha was accepted. Researchers' suggestions that can be given to the community and parents with this research are expected to provide limits for children not to play gadgets too often.